Naringin Stimulates Osteogenic Differentiation of Rat Bone Marrow Stromal Cells via Activation of the Notch Signaling Pathway. (16th March 2016) - Yu, Guo-yong; Zheng, Gui-zhou; Chang, Bo; Hu, Qin-xiao; Lin, Fei-xiang; Liu, De-zhong; Wu, Chu-cheng; Du, Shi-xin; Li, Xue-dong
Abstract : Naringin is a major flavonoid found in grapefruit and is an active compound extracted from the Chinese herbal medicine Rhizoma Drynariae. Naringin is a potent stimulator of osteogenic differentiation and has potential application in preventing bone loss. However, the signaling pathway underlying its osteogenic effect remains unclear. We hypothesized that the osteogenic activity of naringin involves the Notch signaling pathway. Rat bone marrow stromal cells (BMSCs) were cultured in osteogenic medium containing-naringin, with or without DAPT (an inhibitor of Notch signaling), the effects on ALP activity, calcium deposits, osteogenic genes (ALP, BSP, and cbfa1), adipogenic maker gene PPAR γ 2 levels, and Notch expression were examined. We found that naringin dose-dependently increased ALP activity and Alizarin red S staining, and treatment at the optimal concentration (50 μ g/mL) increased mRNA levels of osteogenic genes and Notch1 expression, while decreasing PPAR γ 2 mRNA levels. Furthermore, treatment with DAPT partly reversed effects of naringin on BMSCs, as judged by decreases in naringin-induced ALP activity, calcium deposits, and osteogenic genes expression, as well as upregulation of PPAR γ 2 mRNA levels. These results suggest that the osteogenic effect of naringin partly involves the Notch signaling pathway.